(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
The article deals with significant information about the advantages and disadvantages of monopolies in the economy. On the other hand, basic types of monopoly and main reasons of importance of understanding monopoly markets were discussed.